PENGARUH KOMPENSASI, MOTIVASI DAN STRES KERJA TERHADAP KINERJA KARYAWAN:STUDI KASUS PADA KOMUNITAS KELUARGA GOJEK 24 YOGYAKARTA (2021) - ADHIKA DEVI ARYANI; WIBOWO SETIYO NUGROHO; NUR WENING (FEB Universitas Maritim Semarang, 2022)
Abstract. This study aims to determine the effect of compensation, motivation and work stress on employee performance. The sampling method is purposive sampling method with a sample of 68 respondents. The criteria used in this study are active Gojek drivers, members of the Gojek 24 Yogyakarta community, the second is the main job as a Gojek driver and has no other job. The analytical method used is Multiple Linear Regression Analysis. The results showed that compensation had a positive effect, motivation had a positive effect, and work stress had a negative effect on employee performance. The coefficient of determination shows that 88.8% of compensation, motivation and work stress variables affect employee performance, while the remaining 11.2% is influenced by other variables not examined.